The Particulate Organic Carbon-to-Nitrogen Ratio Varies With Ocean Currents - Xiao, Shengjun; Zhang, Linlin; Teng, Yuhao; Huang, Tao; Luo, Wen (Frontiers in Environmental Science, 2021)
Ocean currents could adjust ocean carbon and nitrogen composition which are an important part of the global carbon and nitrogen cycle. We procured global concentrations of particulate carbon and nitrogen in different depths, classified them according to ocean currents (upper 300 m), and analyzed POC-to-PON ratio (particulate organic carbon-to-nitrogen ratio) variations. We found that the regions with currents have a higher ratio than those without currents in the northern hemisphere, except in 50°–60°N (median ratio without currents is 8.38). Warm currents (median ratio ranges from 5.96 to 8.44) have a higher ratio than cold currents (6.19–8.89), except for the East Greenland Current (reach to 8.44) and Labrador Current (reach to 8.89). Meanwhile, we also analyzed the effects of ocean currents’ flowing and found that the distributions of the POC-to-PON ratio vary in different current types (e.g., cause of formation and distance from the shore). Generally speaking, the POC-to-PON ratio of the eolian currents and near-ocean currents change fiercer than that of compensation currents and near-coast currents. Ocean currents also have a buffering effect in the variation between surface and deep water, which prevents the severe change of the POC-to-PON ratio. The high-value anomaly of POC-to-PON caused by the confluence of warm and cold currents was also analyzed. It can be deduced that the high ratio in the high-latitude region was mainly caused by the terrigenous organic matter (especially carbon) and low nitrogen.